REPRODUCTION OF HOLSTEIN AND BROWN SWISS COWS AND OF THEIR F1 RECIPROCAL CROSSES RAISED IN A MEXICAN SUBTROPICAL ENVIRONMENT - R. C. Calderón-Robles; A. Ríos-Utrera; V. E. Vega-Murillo; M. Montaño-Bermúdez; G. Martínez-Velázquez; S. I. Román-Ponce; R. Calderón-Chagoya (Journal of Animal and Plant Sciences, 2017)
The aim was to assess differences among Brown Swiss (BS), Holstein (HO), BS x HO and HO x BS cows. Age (AFC) and weight at first calving (WFC) were analyzed with a simple model that included sire within breed group (SIRE) as a random effect, and breed group (BG), calving year (CY) and calving season (CS) as fixed effects. Days to first heat, days to first service, days open, calving interval, pregnancy rate at first service (PR), and services per conception (SPC) were analyzed with a repeated measures model that included SIRE (except for SPC and PR), BG, CY, CS, and lactation number. In addition, for PR, the model included stage of lactation (Stage 1: 1 to 50 d; Stage 2: 51 to 100 d; Stage 3: 101 to 150 d; Stage 4: ≥151 d postpartum). Repeated measures model for each trait was fitted testing different covariance structures in order to provide the best fit to the data. The selection of the appropriate covariance structure was based on Akaike’s, second order, Schwarz’s Bayesian and quasilikelihood information criteria fit statistics. Differences among breed groups were found only for AFC and SPC. Holstein and HO x BS cows were younger at first calving (P<0.05) than BS cows (P<0.05). Brown Swiss and BS x HO cows required fewer SPC (P<0.05) than HO cows. Cows in Stage 4 of lactation had higher PR (P<0.05) than cows in Stages 1 and 2 of lactation (63% versus 44% and 50%). Results suggest absence of heterosis effects.
Keywords: Age at first calving; Calving interval; Crossbreeding; Dairy cattle; Pregnancy rate; Subtropics